Hypertrophic Cardiomyopathy and Wolff-Parkinson-White Syndrome in a Young African Soldier with Recurrent Syncope - Mohammed Abdullahi Talle; Faruk Buba; Aimé Bonny; Musa Mohammed Baba (Case Reports in Cardiology)
Syncope is a common manifestation of both hypertrophic cardiomyopathy (HCM) and Wolff-Parkinson-White (WPW) syndrome. The most common arrhythmia in HCM is ventricular tachycardia (VT) and atrial fibrillation (AF). While preexcitation provides the substrate for reentry and supraventricular tachycardia (SVT), AF is more common in patients with preexcitation than the general population. Concurrence of HCM and WPW has been reported in many cases, but whether the prognosis or severity of arrhythmia is different compared to the individual disorders remains unsettled. We report a case of HCM and Wolff-Parkinson-White (WPW) syndrome in a 28-year-old male Nigerian soldier presenting with recurrent syncope and lichen planus.